Economic Evaluation of Robotic-assisted Radical Prostatectomy: A Systematic Review and Meta-analysis - Tanan Bejrananda; Win Khaing; Sajesh K. Veettil; Therdpong Thongseiratch; Nathorn Chaiyakunapruk (European Urology Open Science)
Background and objective: Robotic-assisted radical prostatectomy (RARP) is a surgical option for localized prostate cancer. Cost-effectiveness analysis (CEA) findings are inconsistent when comparing it with open (ORP) and laparoscopic (LRP) radical prostatectomy approaches. We performed a systematic review and meta-analysis to pool the incremental net benefit (INB) of these approaches. Methods: Relevant CEA studies of RARP were identified by searching the PubMed, Embase, Scopus, International Health Technology Assessment database, Tufts CEA Registry, and Centre for Reviews and Dissemination databases from January 2005 to October 2023. To be included, studies must compare costs, and quality-adjusted life years (QALYs) of RARP versus ORP or LRP, and report the incremental cost per QALY gained. Study characteristics, economic model, costs, and outcomes were extracted. INBs were calculated in 2022 US dollars adjusted for purchasing power parity. A pooled analysis was performed using a random-effect model stratified by country income level. Heterogeneity was assessed using the Q test and I2 statistic. Key findings and limitations: Thirteen studies with 17 comparisons, ten from high-income (HICs) and three from middle-income (MICs) countries, were included. Ten and five studies compared RARP with ORP and LRP, respectively. From a payer perspective, RARP was cost effective but not statistically significant compared with LRP in HICs (pooled INB: $7507.83 [–$1193.03 to $16 208.69], I2 = 81.15%) and not cost effective in MICs (%; –$4499.39 [–$16 500 to $7526.87], I2 = 17.15%). RARP showed no statistically significant cost effectiveness over ORP in both HICs ($3322.38 [–$1864.39 to $8509.15], I2 = 90.89%) and MICs ($2222.60 [–$2960.64 to $7405.83], I2 = 58.92%). Conclusions and clinical implications: RARP is cost effective compared with LRP in HICs but lacks statistical significance. When compared with ORP, RARP is not cost effective in HICs and MICs. Our findings may support decision-making for prostate cancer treatment options in countries with different health care systems, especially those with limited resources. Patient summary: Our systematic review and meta-analysis provide important information regarding robotic-assisted radical prostatectomy (RARP) compared with open (ORP) and laparoscopic (LRP) radical prostatectomy. In high-income countries, RARP is generally cost effective compared with LRP, but not with ORP, while in middle-income countries, RARP is not cost effective compared with LRP or ORP. The findings of this review can support decision-making for prostate cancer treatment options.